The Early Late Horizon occupation (400 - 200 BC) in Huanchaco: daily life and ceremonial practices - Prieto, Gabriel (2023)
This paper discusses the domestic and ceremonial occupations during the late Early Horizon in Huanchaco, Moche Valley, North Coast of Peru. A description of the domestic units and their subsistence strategies is presented. The latter includes the exploitation of marine resources, the intense consumption of maize, and the first introduction of camelids in Huanchaco. Ceremonial practices were carried out at the domestic level and in unique buildings shaping “U” shape enclosures, where the dead was also buried. This paper also discusses the emergence of social differentiation among the Huanchaco population during this period and evidence of short, medium, and long-distance trade.